Endometrial cancer in an increasingly obese population: Exploring alternative options when surgery may not cut it - Jeanine N. Staples; Lisa Rauh; M. Sean Peach; William D. Baker; Susan C. Modesitt (Elsevier, 2018)
Objectives: The study objectives were to describe outcomes of obese patients with early endometrial cancer following primary non-surgical treatment, assess predictors of response, and estimate the increased surgical risk for these women. Methods: Retrospective chart review identified women with early stage endometrial cancer at a single institution with BMI ≥ 30 kg/m2 who did not undergo surgery as primary treatment modality due to obesity and medical co-morbidities. Clinicopathologic factors were abstracted, characteristics of responders vs. non-responders compared and the National Surgical Quality Improvement Program (NSQIP) surgical risk calculator utilized to quantify surgical risks. Results: Fifty-one patients were identified, with a mean BMI of 49.0 kg/m2. The NSQIP calculator predicted a significantly higher complication rate for our cohort compared to the expected average risk for hysterectomy (18.8% vs 7.2%, p < .0001). The majority of patients were treated with radiation alone (49%), followed by hormone therapy (45.1%). Response rates were 38.1% for women treated with hormones and 63.6% in the radiation group (p = .063). No significant differences were identified between responders and non-responders with regard to NSQIP scores, BMI, co-morbidities or age. Among those with persistent or progressive disease, 87.5% responded to secondary treatment. Only one death was from cancer progression. Two individuals died following treatment complications (one surgical, one chemotherapy); the remaining twelve deaths were due to pre-existing co-morbidities. Conclusions: Hormone and radiation therapy are both viable options for obese patients deemed to have too significant risk of surgical complications. Pursuing surgical intervention in this population may do more harm than good. Keywords: Obesity, Endometrial cancer, Hormonal therapy, Medically inoperable, NSQIP